Synergy of co-sensitizers in a copper bipyridyl redox system for efficient and cost-effective dye-sensitized solar cells in solar and ambient light. Issue 3 (20th December 2019) - Tanaka, Ellie; Michaels, Hannes; Freitag, Marina; Robertson, Neil
Abstract : Co-sensitization can reduce the cost of a dye-sensitized solar cell, while maintaining high efficiency: up to 29% in ambient light. Abstract : Dye-sensitized solar cells (DSSCs) have a great potential to expand the area of photovoltaics towards portable or indoor applications. Since the dye is one of the most costly components in the device, it is always of interest to find ways to lower its associated cost. Here, we propose the co-sensitization technique as a simple and effective solution towards this aim. A less-expensive π–A dye (5T) was mixed with a better-performing D–A–π–A dye (XY1) to fabricate the co-sensitized devices (XY1 + 5T). The dyes were combined with a Cu I/II (tmby)2 (tmby = (4, 4′, 6, 6′-tetramethyl-2, 2′-bipyridine)) electrolyte and tested at 1 sun and 0.1 sun conditions. The XY1 + 5T devices showed similar power conversion efficiency (PCE) to that of the XY1-only devices at 1 sun (avg. 9.1%), and superior PCE at 0.1 sun (avg. 9.4% vs. 8.6%). The charge transport behaviour in the devices was investigated through a combination of photophysical measurements, which revealed complementary effects of both dyes during device operation. The performance of XY1 + 5T at lower light intensity was further assessed using artificial fluorescent lighting, which marked a PCE as high as 29.2% at 1000 lux, among the highest reported. Finally, the cost of dye was estimated to be reduced by ca. 30% if an XY1-only device is replaced by XY1 + 5T with no loss in efficiency. The cost-performance is thus improved 1.4 times. Our findings will revalue the co-sensitization method as a means to address the challenges of DSSC commercialization.